2010
DOI: 10.1007/s10551-011-1074-8
|View full text |Cite
|
Sign up to set email alerts
|

Community Development and Social Regeneration: How the Third Sector Addresses the Needs of BME Communities in Post-Industrial Cities

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…SE created by traditionally disadvantaged groups can also be considered as lesser: lacking the capacity to create robust, sustainable social and public goods. A CA-based study of such organizations showed clearly that these assumptions, themselves grounded in a “disadvantaged-as-less-capable” perspective, was misguided (Wallace & Cornelius, 2010 ).…”
Section: Inequality Re-examined: the Influence Of The Capability Appr...mentioning
confidence: 99%
“…SE created by traditionally disadvantaged groups can also be considered as lesser: lacking the capacity to create robust, sustainable social and public goods. A CA-based study of such organizations showed clearly that these assumptions, themselves grounded in a “disadvantaged-as-less-capable” perspective, was misguided (Wallace & Cornelius, 2010 ).…”
Section: Inequality Re-examined: the Influence Of The Capability Appr...mentioning
confidence: 99%
“…Further, although increasingly, academics and practitioners are becoming increasingly sensitive to the needs for SEs to be well run and governed (Cornelius et al , 2008; Wallace and Cornelius, 2010; Low, 2006; Mason et al , 2007) less attention has been made regarding the strictures that could be set by governments that choose to sub‐contract responsibility for social action to SEs. We suggest that there needs to be a clear agreement at the stage of contracting with government agencies.…”
Section: Political Environment and Policy Developmentmentioning
confidence: 99%
“…However, where established institutions have failed, third sector organisations such as SEs may be more effective (Cornelius and Wallace, 2011, 2012; Wallace and Cornelius, 2010; Spear and Bidet, 2005; Ridley‐Duff and Bull, 2011). For example, Jan‐Khan, 2003 praises the ethnic third sector, arguing that “a strong and vibrant black and minority ethnic voluntary sector which has served the specific needs of [these] communities in their own geographically based areas” (Jan‐Khan, 2003, p. 33).…”
Section: Introductionmentioning
confidence: 99%